1989
DOI: 10.1111/j.1432-1033.1989.tb14994.x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Glutamylcyclotransferase: inhibition by d‐β‐aminoglutaryl‐l‐alanine and analysis of the solvent kinetic isotope effect

Abstract: Spin-echo NMR spectroscopy was used to record the cleavage of a gamma-glutamyl--amino-acid by (5-L-glutamyl)-L-amino-acid 5-glutamyltransferase (cyclizing) (gamma-glutamylcyclotransferase) in human erythrocyte hemolysates. The Michaelis-Menten steady-state kinetic parameters were obtained by fitting the integrated Michaelis-Menten equation to the reaction time curves. The product, L-5-oxoproline, was shown to be an inhibitor of the reaction. The active site of the enzyme was probed by studies of the inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In previous studies, we reported on novel inhibitors of GGCT enzymatic activity. N ‐Glutaryl‐ l ‐alanine (GA) and other compounds inhibit GGCT activity in vitro, which can be measured using multistep reaction methods or with the originally developed GGCT probe, LISA‐101 . However, a major obstacle of using these candidate compounds as anticancer agents is that they are unable to penetrate living cell membranes efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we reported on novel inhibitors of GGCT enzymatic activity. N ‐Glutaryl‐ l ‐alanine (GA) and other compounds inhibit GGCT activity in vitro, which can be measured using multistep reaction methods or with the originally developed GGCT probe, LISA‐101 . However, a major obstacle of using these candidate compounds as anticancer agents is that they are unable to penetrate living cell membranes efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Among 113 missing enzyme genes in the cattle metabolic pathways, the activities of six enzymes were reported in cattle (Table 4 ) [ 21 - 38 ]; 16 enzyme activities were reported in other mammals but not in cattle (Table 5 ) [ 39 - 67 ]. However, in both cases, corresponding mammalian genes have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…This paper reports the synthesis of (3S)-3-aminoglutaryl-(S)alanine (8), (3R)-3-aminoglutaryl-(S)-alanine (14), and (3R)-3aminoglutaryl-(S)-alaninol (22). These three dipeptides were required for structure-activity and inhibition studies on GCT.…”
mentioning
confidence: 99%
“…Two routes to the dipeptides (8) and (14) have been investigated in this work. The preferred route is selective and makes use of an enzyme-catalysed cleavage of the prochiral diester (3) to the chiral half-ester (4) (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation